Pengembangan Model Layanan Penguasaan Konten Berbasis Ajaran Islam untuk Meningkatkan Motivasi Belajar Siswa - Gozali, Achmad (Universitas Islam Bunga Bangsa Cirebon, 2020)
Motivation to learn is one of the main factors in learning. Students who are less motivated to learn more likely to avoid learning and academic failure. So that the necessary services to treat the condition, such as mastery of content services based on Islamic teachings attribution exercise. The purpose of this study are to: 1) know the description of service implementation mastery of content; 2) determine the level of motivation to learn; 3) generate a service model based content mastery Islamic teaching to enhance learning motivation; 4) determine the effectiveness of the model in increasing motivation to learn. This study uses research and development methods with research steps include: preliminary studies, design a hypothetical model, due diligence hypothetical model, repair hypothetical model, field tests, hypothetical model finished product; and test the effectiveness of the model. The results showed that 1) the service content mastery been implemented in schools, but not in accordance with the work program; 2) the level of student motivation before being treated with an average in the category fairly and less; 3) generate a service model based content mastery Islamic teaching to improve students' motivation in high school, which consists of eight components, namely the rational, vision and mission, objectives, content, support systems, stages of implementation, evaluation, and follow-up; 4) the service model mastery of Islamic teachings based content effectively to improve student motivation. Keywords: Motivation; Learning; Atribution Retraining. Abstrak Motivasi belajar merupakan salah satu faktor utama dalam belajar. Siswa yang kurang termotivasi belajar cenderung akan menghindari kegiatan belajar dan mengalami kegagalan akademik. Sehingga diperlukan layanan untuk mengatasi kondisi tersebut, misalnya layanan penguasaan konten tentang latihan atribusi berbasis ajaran Islam. Tujuan penelitian ini yaitu untuk: 1) mengetahui gambaran pelaksanaan layanan penguasaan konten; 2) mengetahui tingkat motivasi belajar; 3) menghasilkan model layanan penguasaan konten berbasis ajaran Islam untuk meningkatkan motivasi belajar; 4) mengetahui tingkat keefektifan model dalam meningkatkan motivasi belajar. Penelitian ini menggunakan metode penelitian pengembangan dengan langkah penelitian, meliputi: studi pendahuluan, merancang model hipotetik, uji kelayakan model hipotetik, perbaikan model hipotetik, uji lapangan, model hipotetik hasil akhir produk; dan uji efektivitas model. Hasil penelitian menunjukkan bahwa 1) layanan penguasaan konten pernah dilaksanakan di sekolah, namun belum sesuai dengan program kerja; 2) tingkat motivasi belajar siswa sebelum diberi perlakuan yaitu rata-rata pada kategori cukup dan kurang; 3) menghasilkan model layanan penguasaan konten berbasis ajaran Islam untuk meningkatkan motivasi belajar siswa di SMA, yang terdiri dari 8 komponen, yaitu rasional, visi dan misi, tujuan, isi, dukungan sistem, tahapan pelaksanaan, evaluasi, dan tindak lanjut; 4) model layanan penguasaan konten berbasis ajaran Islam efektif untuk meningkatkan motivasi belajar siswa. Kata Kunci: Motivasi Belajar; Latihan Atribusi; Layanan Penguasaan Konten.